Analisando o desqualificável : um estudo sobre pedido de desculpas de figuras públicas em redes sociais - Giovana Perini Frizera de Morais Loureiro (2021)
Virtual communication is fundamental for society nowadays and the strategies used in social media are different from the ones in face-to-face interactions, being carried out according to the users’ interactional goals. The present study sought to describe the strategies employed and the linguistic motivations behind the construction of apologies on social networks by public figures in Brazilian Portuguese and American English. We consider apologies as remedial speech events associated with Politeness, subsequent to possible offenses. The speaker’s intention when issuing an apology is to repair an action considered impolite by the community of practice and restore harmony in the interaction (LEECH, 2014). Apologies seek to maintain and enhance the Face of those involved, as part of the relational work, negotiating the construction of the Face of all participants (HAUGH, 2013). Relational work arising from human interactions refers to the constant practice of negotiating relationships with other participants, and polite behaviour is part of this work (LOCKER, 2006). This research focused on the construction and analysis of a corpus comprising of 100 apologies, 50 in Brazilian Portuguese and 50 in American English posted on Twitter, Facebook and Instagram by public figures. Each apology was categorized into speech acts and the strategies employed were investigated through qualitative analysis under a pragmatic interactional perspective. The study of the corpus allowed us to survey a descriptive flowchart of the strategies used to apologize publicly in both languages on social networks. As a result, it was noticed the consistent use of speech acts in the speech event ‘apologies’, as proposed by Blum-Kulka and Olshtain (1984) – such as acknowledging responsibility and explaining the offense event. Furthermore, the flowchart created based on the qualitative analysis of the data obtained also presents the Politeness strategies most used when apologizing. Finally, differences were noted in the realization of apologies and the frequency of strategies used between the data in English and Portuguese, following what is expected and judged as polite by the communities of practice in which the interaction takes place (SPENCER-OATEY, 2002). The understanding and description of apologies in virtual environments sheds light on digital interactional practices and their pragmatic motivations, contributing to the studies of language in use and to the perception of Politeness expectations of the observed communities of practice.